Impact of Pet Ownership and Relationships on Human Psychological Health and Function - Bhatia, (Maj) Deepak; Bhatia, Akansha; Sarma, Dhritiman (Gyan Management Journal, 2022)
Numerous studies have examined the effects of “pet /companion ownership and pet interactions on human psychological health and function”. Recent study on “the benefits of pets and human-animal interaction for mental health has discovered new benefits for managing stress, depression, and post-traumatic stress, as well as for stress reduction”. Interacting with animals has been demonstrated to reduce cortisol levels (a hormone associated with stress) and blood pressure. Other studies have discovered that pets help alleviate feelings of isolation, promote emotions of social support, and improve your happiness. “The biopsychosocial model has been widely used for over 40 years to describe how biological, psychological, and social processes interact to affect human health and wellbeing. Biological impacts are physiological changes, including blood pressure, cortisol, and heart rate, among others. Among the psychological influences are personality, disposition, and emotions. The term social influences refer to cultural, socioeconomic, and social ties with others, as well as family dynamics and aspects related”.